PENGARUH PERCEIVED VALUE DA NCUSTOMER SATISFACTION TERHADAP LOYALITAS PELANGGAN (STUDI PADA PELANGGAN TOP SWALAYAN KOLAKA) - Amir, Sarlinda; Titing, Andry Stepahnie; Zul Bay, Agus (LPPM STIE EKA PRASETYA, 2025)
The purpose of this study was to determine: (1) The effect of perceived value on customer loyalty at TOP Swalayan Kolaka. (2) The effect of customer satisfaction on customer loyalty at TOP Swalayan Kolaka. This research model is explanatory research with a quantitative approach. Data collection techniques in this study through interviews, questionnaires, and literature studies. The population of this study were all people in Kolaka Regency. While the sample in this study were 100 respondents using purposive sampling technique. In this study, validity and reliability checking tools were used with SPSS 30.0. Structural Equating Modeling (SEM), which is based on Partial Least Square (PLS), was used for data analysis. Smart PLS 4.0 was used for the outer model and outer structural model checks. Based on the research results, the P-Value of 0.003 indicates that there is a positive and significant influence between the perceived value variable on customer loyalty and the customer satisfaction variable also has a positive and significant effect on customer loyalty, this is indicated by the P-Value of 0.000.